Neoteric Solvents for Metal-Catalyzed Coupling Reactions - Langellotti, Vincenzo; Melchiorre, Massimo; Cucciolito, Maria Elena; Esposito, Roberto; Ruffo, Francesco (SynOpen, 2025)
Catalysis is a green methodology aimed at optimizing synthetic procedures by simplifying the design of target molecules and reducing energy and material consumption. However, catalytic reactions often rely on polar aprotic solvents, such as dimethylformamide (DMF) or acetonitrile, which present environmental and health issues. In response, manufacturers and researchers are exploring greener alternatives derived from residual biomass, which reduce the negative environmental impact of traditional solvents. These new classes of solvents are termed ‘neoteric’ in order to distinguish them from traditional solvents with well-established applications. This graphical review highlights key findings on the use of these new solvents in metal-catalyzed coupling reactions.
Keywords: coupling; catalysis; green chemistry; solvents; biomass